2012
DOI: 10.1007/s00284-012-0174-8
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Comparison of Two Virus Concentration Methods from Wastewater Using Cell Culture and Real-Time PCR

Abstract: Enteric viruses are shed in the feces and may be present in environmental waters. Their detection in wastewater, even at low concentration, is a major challenge. In this study, recoveries of Echovirus 7 (EV7), virions and RNA in wastewater, using virus concentration methods were determined to evaluate the detection of infectious viruses and the possibility of recovering viral genomes. Two virus concentration methods, PEG precipitation method and two-phase separation method, were applied to recovery experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Some of them advised EV (37,50) and others advised HAdV (38,51) . Current study results are in agreement with those obtained in previous study when the same methods were compared using Echovirus 7 as a model of enteroviruses (22) .…”
Section: Presence Of Infectious Ev and Hadv In Raw Wastewater And Tresupporting
confidence: 83%
See 3 more Smart Citations
“…Some of them advised EV (37,50) and others advised HAdV (38,51) . Current study results are in agreement with those obtained in previous study when the same methods were compared using Echovirus 7 as a model of enteroviruses (22) .…”
Section: Presence Of Infectious Ev and Hadv In Raw Wastewater And Tresupporting
confidence: 83%
“…The obtained results showed that Hep2 cells were more suitable for adenovirus detection as reported in previous study (22) . The use of both cell lines was useful for us to isolate the most of HAdV and EV in samples.…”
Section: Presence Of Infectious Ev and Hadv By Cell Culturesupporting
confidence: 71%
See 2 more Smart Citations
“…An effective concentration of samples is necessary to evaluate virological quality of wastewaters, since matrices are highly contaminated with inhibitory substances that will interfere with viral detection [11]. Numerous methods have been described for concentrating and extracting enteric viruses from sewage [14][15][16]. All of them studied on spiked viral particles in decontaminated samples.…”
Section: Introductionmentioning
confidence: 99%